Ferritic heat-resistant steel with both high-temperature strength and oxidation resistance
A tailored ferritic steel composition with controlled alloying elements enhances high-temperature strength and oxidation resistance by segregating boron at grain boundaries, addressing the limitations of conventional steels in high-temperature environments.
Patent Information
- Application Number
- JP2020215383
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-24
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2040-12-24
AI Technical Summary
Conventional ferritic steels face challenges in achieving high-temperature strength and oxidation resistance, especially at temperatures above 800°C, while maintaining economic efficiency, due to issues with alloying element precipitation and segregation, which affect both strength and corrosion resistance.
A ferritic heat-resistant steel composition with specific alloying elements (C, Si, Mn, P, S, Cr, Mo, W, Al, Ti, Nb, N, and B) is formulated to segregate boron at grain boundaries, suppressing intermetallic compound precipitation and enhancing grain boundary strengthening and precipitation strengthening, thereby improving high-temperature strength and oxidation resistance.
The steel achieves excellent high-temperature strength and oxidation resistance, with optimized alloying to prevent detrimental precipitation, ensuring both properties are maintained without compromising economic efficiency.
Smart Images

Figure 0007599781000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic heat-resistant steel having excellent high-temperature strength and oxidation resistance for use in high-temperature and corrosive combustion gas environments such as recuperator heat exchangers and other heat balance enhancing heat exchangers and high-temperature exhaust systems. [Background technology]
[0002] In conventional heat exchangers that increase the heat balance such as recuperators and exhaust systems for various high-temperature gases, the maximum temperature of the metal in the operating environment was about 750°C. Therefore, the DIN standard steel type X, known as ferritic heat-resistant steel (Cr-Si-Al steel), was selected as a steel material that could withstand this temperature range. 10 CrAl 24 etc. are being used.
[0003] To further improve thermal efficiency, it is necessary to raise the operating temperature, for example to 800°C or higher. However, because oxidation and corrosion in high-temperature environments cause significant thinning of steel materials, steel materials are required to have higher resistance to high-temperature oxidation, as well as excellent high-temperature strength that satisfies the design strength in high-temperature environments and suppresses deformation.
[0004] Although austenitic stainless steels and Ni-based alloys are considered to be useful as steel materials with high temperature resistance, they are not economically superior because they contain large amounts of alloying elements such as Ni.
[0005] On the other hand, ferritic stainless steel is economical because it contains a small amount of alloying elements such as Ni. Therefore, a method of improving high-temperature strength by adding rare metals such as Hf, Zr, Ta, and Os to ferritic stainless steel has been proposed (for example, see Patent Document 1).
[0006] However, this proposal only evaluated creep strength at 650℃, and its applicability in higher temperature environments is unclear. In addition, the carbonitrides that are said to contribute to high-temperature strength generally precipitate quickly, so their strengthening effect at higher temperatures is small, and it is not expected that the operating temperature of the current recuperator heat exchanger will be raised. In addition, rare metals are highly valuable, which worsens the economic efficiency, and there are concerns about the procurement of rare metals, so there is an issue with the stable supply of raw materials. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 11-61342 Summary of the Invention [Problem to be solved by the invention]
[0008] In ferritic stainless steel and ferritic heat-resistant steel, alloy elements such as Mo, W, Nb, and Ti are sometimes added to utilize the material strengthening mechanisms of solid solution strengthening and precipitation strengthening by intermetallic compounds in order to improve high-temperature strength. Alternatively, grain boundary segregation of P, S, and other elements can reduce oxidation resistance and secondary workability, but in order to suppress this, boron (B), which segregates preferentially at grain boundaries and is effective in increasing strength through grain boundary strengthening, is sometimes added.
[0009] Combining these approaches in alloy design may result in steels with excellent oxidation resistance and high-temperature strength, but there is a problem in that the precipitation of intermetallic compounds competes with the precipitation of boron compounds, which are not expected to improve high-temperature strength or oxidation resistance.
[0010] Therefore, if it were possible to segregate boron to grain boundaries while suppressing the precipitation of boron compounds, which competes with the precipitation of intermetallic compounds, it would be expected that the precipitation strengthening due to the precipitation of intermetallic compounds and the grain boundary strengthening due to the grain boundary segregation of boron would maximize the effect of improving high-temperature strength, and that excellent oxidation resistance would be realized due to the precipitation of intermetallic compounds that does not reduce oxidation resistance. However, a specific method for achieving this has not yet been found.
[0011] The problem to be solved by the present invention is to provide a ferritic heat-resistant steel which is excellent in high-temperature strength, oxidation resistance and economy. [Means for solving the problem]
[0012] The first means for solving the problems of the present invention is This ferritic heat-resistant steel is composed, by mass%, of C: 0.001 to 0.040%, Si: 0.4 to 1.2%, Mn: 0.01 to 1.00%, P: 0.040% or less, S: 0.030% or less, Cr: 21.5 to 26.0% or less, Mo: 0.01 to 1.50%, W: 0.01 to 2.00%, Al: 0.6 to 1.4%, Ti: 0.01 to 0.90%, Nb: 0.01 to 0.90%, N: 0.05% or less, B: 0.0001 to 0.0150%, and the balance being Fe and unavoidable impurities.
[0013] The second means is a ferritic heat-resistant steel having the chemical composition according to the first means, further characterized in that the relationship between formulas (1) and (2) is satisfied. 125 × [B] ≦ [Ti] formula (1) [Ti]≦(1 / 1174)×(7735-([Si]+289.1×[Cr]+48.5×[Mo]+375.5×[Al]+12.2×[W]+9.1×[Nb]+5000×[B]))...Equation (2) In addition, the mass% value of each alloying element is substituted for the [element symbol] in the formula. Effect of the Invention
[0014] According to the present invention, the effect of improving high-temperature strength and oxidation resistance is not obtained. 2 Intermetallic compounds that suppress the crystallization or precipitation of Ti and instead improve high-temperature strength without reducing oxidation resistance, such as (Fe, Cr, Si) 2 The precipitation of the Laves phase represented by (Nb, Ti, Mo, W) at grain boundaries and within grains achieves both grain boundary segregation of boron and precipitation of intermetallic compounds, thereby realizing grain boundary strengthening and precipitation strengthening by the precipitation of intermetallic compounds, thereby obtaining excellent high-temperature strength, while excellent oxidation resistance can be obtained by the precipitation of intermetallic compounds that do not reduce oxidation resistance, such as the Laves phase. Thus, a ferritic heat-resistant steel with excellent high-temperature strength, oxidation resistance, and economy can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] First, the reasons for defining the chemical compositions of the heat-resistant steel of the present invention and the reasons for defining formulas (1) and (2) will be explained below.
[0016] C: 0.001 to 0.040% C is an element necessary for ensuring strength. However, if C exceeds 0.040%, workability decreases. Therefore, C is set to 0.001 to 0.040%.
[0017] Silicon: 0.4 to 1.2% Silicon is an element that improves oxidation resistance. To achieve this, the silicon content must be 0.4% or more. On the other hand, if the silicon content exceeds 1.2%, the workability decreases. Therefore, the silicon content is set to 0.4 to 1.2%.
[0018] Mn: 0.01 to 1.00% Mn is an element that improves oxidation resistance and scale spalling resistance. However, if it exceeds 1.00%, a gamma phase, which is the starting point of abnormal oxidation, is formed. In addition, the gamma phase has a larger thermal expansion coefficient than the alpha phase, so dimensional change is large. Therefore, the Mn content is set to 0.01 to 1.00%.
[0019] P:≦0.040% P is an element that is mixed into steel as an inevitable impurity, but if the P content exceeds 0.040%, hot workability decreases, so the P content is set to 0.040% or less.
[0020] S:≦0.030% S is an element that is mixed into steel as an inevitable impurity, but if the S content exceeds 0.030%, hot workability decreases. Therefore, the S content is set to 0.030% or less.
[0021] Cr: 21.5~26.0% Cr is an element that improves oxidation resistance, and in the present invention, Cr is added at 21.5% or more. However, if Cr exceeds 26.0%, workability decreases. Therefore, Cr is set to 21.5 to 26.0%.
[0022] Mo: 0.01 to 1.50% Mo is an element that improves high-temperature strength. However, if Mo exceeds 1.50%, oxidation resistance decreases. Therefore, Mo is set to 0.01 to 1.50%.
[0023] W: 0.01 to 2.00% W is an element that improves high-temperature strength and oxidation resistance. However, if W exceeds 2.00%, it reduces oxidation resistance and workability. Therefore, W is set to 0.01 to 2.00%.
[0024] Al: 0.6-1.4% Al is an element that improves oxidation resistance, and 0.6% or more is necessary. However, if it exceeds 1.4%, workability decreases. Therefore, the Al content is set to 0.6 to 1.4%.
[0025] Ti: 0.01 to 0.90% Ti is an element that improves high-temperature strength through solid solution strengthening and precipitation strengthening using intermetallic compounds (e.g., Laves phase), and is also effective in improving oxidation resistance. However, Ti is a strong carbonitride forming element, and if the content in steel exceeds 0.90%, carbonitrides tend to crystallize or precipitate, which becomes the starting point for abnormal oxidation and leads to a decrease in oxidation resistance, and at the same time, it leads to an excessive increase and coarsening of the precipitation amount of intermetallic compounds (e.g., Laves phase), which inhibits the grain boundary segregation of boron, and therefore excellent high-temperature strength is not exhibited. Therefore, Ti is set to 0.01 to 0.90%.
[0026] Nb: 0.01 to 0.90% Nb is an element necessary for improving high-temperature strength by solid solution strengthening and precipitation strengthening using intermetallic compounds (e.g., Laves phase), and 0.01% or more is required. However, Nb is a strong carbonitride forming element, and if the content in steel exceeds 0.90%, carbonitrides tend to crystallize or precipitate, which become the starting point for abnormal oxidation, leading to deterioration of oxidation resistance and reduction in high-temperature strength. Therefore, the Nb content is set to 0.01 to 0.90%.
[0027] N:≦0.05% N is an element that is mixed in as an impurity. If the N content exceeds 0.05%, the amount of precipitates of Ti and Nb compounds increases, and the high-temperature strength decreases. Therefore, the N content is set to 0.05% or less.
[0028] B: 0.0001 to 0.0150% B is an element that strengthens grain boundaries and improves high-temperature strength, and 0.0001% or more is required. However, if B exceeds 0.0150%, 2 This leads to the crystallization or precipitation of Ti, which prevents the excellent oxidation resistance and high-temperature strength from being exhibited. Therefore, the B content is set to 0.0001 to 0.0150%.
[0029] Formula (1): 125 × [B] ≦ [Ti] Formula (1) is an index of improved oxidation resistance. When formula (1) is satisfied, the amount of solute Ti is large and Ti is concentrated near the oxide scale, which forms on the surface of steel used at high temperatures. This inhibits the phenomenon in which oxygen from the steel's operating environment diffuses into the steel and causes the oxide scale to grow. Excellent oxidation resistance is obtained by having a large amount of solute Ti and by having Ti concentrate near the oxide scale. and On the other hand, if equation (1) is not satisfied and the value of the right side is smaller than the value of the left side, then B 2 Since the amount of Ti dissolved in the steel material is reduced by the crystallization or precipitation of Ti, the effect of inhibiting the growth of oxide scale by the dissolved Ti as described above becomes insufficient, and the effect of improving oxidation resistance cannot be obtained.
[0030] Formula (2): [Ti]≦(1 / 1174)×(7735-([Si]+289.1×[Cr]+48.5×[Mo]+375.5×[Al]+12.2×[W]+9.1×[Nb]+5000×[B])) Equation (2) is an index of the effect of grain boundary strengthening, that is, the improvement of high-temperature strength. If the value on the right side of equation (2) is smaller than the value of Ti, the grain boundary precipitation of intermetallic compounds, typified by the Laves phase, increases and coarsens, making it difficult for the grain boundary segregation of B to coexist. In other words, the effect of grain boundary strengthening due to the coexistence of intermetallic compounds and grain boundary segregation of B, in other words, the effect of improving high-temperature strength, cannot be obtained.
[0031] (Example) For the ferritic heat-resistant steels of Examples Nos. 1 to 17 and the steels of Comparative Examples Nos. 18 to 26, which are made of the chemical compositions shown in Table 1, steel ingots were melted using a 100 kg VIM (vacuum induction melting method), heated to 1100°C, forged into a prism shape with a square of 15 mm, held at 1100°C for 15 minutes, and then water-cooled to prepare predetermined test pieces, and the high-temperature strength and oxidation resistance were evaluated. In Table 1, the cases where each steel of the Examples and Comparative Examples satisfied the formulas (1) and (2) are indicated with ◯, and the cases where it did not are indicated with ×.
[0032] [Table 1]
[0033] The evaluation of high-temperature strength was carried out in the following manner based on the high-temperature tensile test method specified in JIS G 0567. For each of the examples and comparative examples, high-temperature tensile test pieces with a parallel part diameter of 6 mm were prepared, and after heating the test pieces to 850°C, tensile stress was applied to the test pieces until they broke, and the maximum stress at this time was determined as the high-temperature tensile strength. In Table 1, those with a high-temperature tensile strength of 50 MPa or more are shown as excellent high-temperature strength with a circle, and those with a high-temperature tensile strength of less than 50 MPa are shown as inferior high-temperature strength with a cross.
[0034] The oxidation resistance was evaluated by a 100-hour continuous oxidation test described below. For each of the steels of the examples and comparative examples, a test piece with a diameter of 21 mm and a length of 12 mm was prepared, and the surface properties were adjusted with 320-600 grit abrasive paper, and the weight of the test piece was measured. Next, a continuous oxidation test was performed in which the test piece was held in an electric furnace in an air atmosphere heated to 1200°C for 100 hours and cooled to room temperature. After the test, the surface scale of the test piece was removed by shot blasting, and the weight of the test piece was measured. The reduction in the weight of the test piece before and after the test was used as an evaluation index for oxidation resistance. In Table 1, specimens with a weight loss of 50 mg or less per unit area are indicated by a circle (◯) as having excellent oxidation resistance, and specimens with a weight loss of 50 mg or more are indicated by an X as having poor oxidation resistance.
[0035] In Table 1, as a comprehensive judgment, those which are inferior in either high-temperature strength or oxidation resistance (indicated with an x) are indicated with an x as they do not achieve both.
[0036] In the examples of the present invention, Nos. 1 to 17, steels excellent in high-temperature strength and oxidation resistance were obtained.
[0037] On the other hand, Comparative Example No. 18 had excessive Ti and N and the value of formula (2) was outside the range specified by the present invention, so that the high-temperature strength was reduced. In Comparative Example No. 19, the values of formulas (1) and (2) were out of the range, and the high-temperature strength and oxidation resistance were reduced. In Comparative Example 20, the B content was excessive, the Cr content was too small, and the value of formula (1) was also outside the specified range, resulting in reduced oxidation resistance. In Comparative Example 21, the Si content was too small and the Mn content was too large, so the oxidation resistance was reduced, and since B was not included, the high-temperature strength was reduced. In Comparative Example 22, the value of formula (2) was outside the specified range, and the high-temperature strength was reduced. In Comparative Example 23, Nb was not contained, and the value of formula (2) was outside the specified range, so that the high-temperature strength was reduced. In Comparative Example 24, the Mo content was excessive, and the values of formulas (1) and (2) were outside the prescribed ranges, so that the high-temperature strength and oxidation resistance were reduced. In Comparative Example 25, the Cr content was too small, the Mo content was too large, the Al content was too small, Ti was not contained, and the value of formula (1) was outside the specified range, so that the high-temperature strength and oxidation resistance were reduced. In Comparative Example 26, the value of formula (1) was also outside the specified range, and therefore the oxidation resistance was reduced.
Claims
[Claim 1] In mass%, C: 0.001 to 0.040%, Si: 0.4 to 1.2%, Mn: 0.01 to 1.00%, P: 0.040% or less, S: 0.030% or less, Cr: 21.5 to 26.0% or less, Mo: 0.01 to 1.50%, W: 0.01 to 2.00%, Al: 0.6 to 1.4%, Ti: 0.01 to 0.90%, Nb: 0.01 to 0.90%, N: 0.05% or less, B: 0.0001 to 0.0150%, and the balance being Fe and unavoidable impurities; Furthermore, the relationship of formula (1) and formula (2) is satisfied. Ferritic heat-resistant steel characterized by: 125×[B]≦[Ti]...Formula (1) [Ti]≦(1 / 1174)×(7735-([Si]+289.1×[Cr]+48.5×[Mo]+375.5×[Al]+12.2×[W]+9.1×[Nb]+5000×[B]))...Formula (2) In addition, the mass percentage of each alloying element is substituted for the [element symbol] in the formula.
Citation Information
Patent Citations
High chromium ferritic steel
JP1999061342A
Heat-transfer material for heat collection, and its manufacturing method
JP2008101240A
Ferritic stainless steel and method for producing the same, and fuel cell member
JP2018080371A
Ferritic stainless steel for use in fuel reformer and method of manufacturing ferritic stainless steel
WO2015064739A1
Al-CONTAINING FERRITIC STAINLESS STEEL WITH EXCELLENT CREEP CHARACTERISTICS, MANUFACTURING METHOD THEREFOR, AND FUEL CELL MEMBER
WO2017073094A1
